I will be right here - All-4-One; Atlantic Recording Corporation; WARNER Music (Malaysia). (United States : Atlantic Recording Corporation, 1998)
Contains the single which is taken from the album'On And On'.
CD 1 : I Will Be Right Here / (4:24).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English